Potentiodynamic Corrosion Behavior and Microstructural Characteristics of Pulsed CMT-Welded AA2014-T6 Aluminium Alloy Joints: Effect of PWHT - A. Padma Rao; Manzoor Hadi; C. Rajendran; Sonar Tushar; Mikhail Ivanov; P. Senthil Kumar; V. Murali Krishna (Advances in Materials Science and Engineering)
AA2014-T6 is an Al-Cu-Mg-based precipitation-hardened aluminium alloy widely used in aerospace due to its high strength to weight ratio. This alloy is joined by a pulsed cold metal transfer (PCMT) arc welding process to overcome the high heat input related problems in gas metal arc welding (GMAW) such as a coarser dendritic structure in the fusion zone (FZ), wider heat affected zone (HAZ), solidification and HAZ liquation cracking, softening in HAZ, and poor corrosion resistance of welded joints in salt environment. The joints were subjected to PWHT of artificial aging (AA), solution treatment (ST), and solution treatment + aging (STA) conditions. The corrosion rate was determined using a potentiodynamic corrosion test in a solution of 3.56 wt.% NaCl with pH values of 4, 7, and 11. Results disclosed that the PCMT joints subjected to the potentiodynamic corrosion test in NaCl solution of pH-4, pH-7, and pH-11 disclosed very low, moderate, and extremely high pitting corrosion, respectively. The corrosion resistance of ST joints was improved by 53.34%, 15%, and 15.12% in pH-4, pH-7, and pH-11 NaCl solution compared to as-welded joints. The pitting potential of ST joints is comparable to BM. The BM showed the pitting potential of −175, −450, and −550 mV in pH-4, pH-7, and pH-11 NaCl solution. The ST joints showed 75.29%, 29.16%, and 27.85% lower corrosion potential compared to STA joints in pH-4, pH-7, and pH-11 NaCl solution, respectively. The ST joints disclosed the lower pitting potential of −105, −425, and −505 mV in pH-4, pH-7, and pH-11 NaCl solution, respectively, whereas the STA joints revealed greater pitting potential of −425, −600, and −700 mV in pH-4, pH-7, and pH-11 NaCl solution, respectively. The superior corrosion resistance of ST joints compared to AA and STA joints is attributed to the dissolution of precipitates in Al solid solution resulting in a lower potential difference in FZ. This minimizes the preferential sites for pitting corrosion to occur.